Results of the Kosovo 2013 : Labour Force Survey - Kosovo Agency of Statistics (World Bank, Washington, DC, 2014)
The purpose of the Labour Force Survey in Kosovo is to provide statistical data on labor market indicators and enable comparisons to be drawn with previous years. The methodology and definitions applied in the LFS are the same as those used in 2012 and is consistent with Eurostat regulations. The LFS survey includes 600 Enumeration Areas throughout the territory of Kosovo where 4,800 households are interviewed. This Labour Force Survey 2013 report contains data on employment and unemployment by age, gender, employment status, economic activities, occupations and other areas of the labor market. At the end of the report section 6 reports on changes of the main indicators between 2012 and 2013. Overall there have not been any dramatic changes, which is to be expected. The unemployment rate has remained virtually unchanged between 2012 and 2013 and it remains higher among women than men. The unemployment rate is higher among young people. Kosovo continues to exhibit challenging labor market performance despite a continued growth rate. Kosovo is one of the transition countries least affected by the global economic crisis, however if the economy slows down this complicates the task of generating new jobs that are needed each year in order to meet the growing number of new entrants into the labor force.